Syphilis frequency and features among newly diagnosed HIV cases - Edjola Lulja; Najada Como; Arjan Harxhi (Journal of Global Antimicrobial Resistance)
BACKGROUND: The incidence of syphilis is rising all over the world, partly due to the increased transmission in HIV patients and other high risk groups such as men who have sex with men Materials: This is a retrospective study carried out at Infectious Disease Service in Tirana, Albania. It aims to assess the prevalence of HIV/syphilis co-infection and describe the epidemiological, clinical and therapeutic features of syphilis diagnosed among newly diagnosed HIV cases during 2023. RESULTS: Out of 100 patients diagnosed with HIV infection, 53 patients were tested at baseline and 15 cases (28.3%) were diagnosed with syphilis. All were male with average age of 38 years (21-58 years). 4 cases (26%) declared homosexual relationships. Median CD4 level at baseline was 280 cells/ul, 5 cases (36%) had CD4 < 200 cells, 11 cases had CD4 < 350 cells. 3 cases (20%) were presented as primary syphilis, 7 cases (47%) as secondary syphilis and 5 cases (33%) as latent. Clinical signs included primary chancre, inguinal lymphadenopathy, systemic lymphadenopathy, maculo-papular, nodular rash. In two cases uveitis was described. Diagnosis was made by serology tests where the highest titer of RPR was 1:64. Therapy was carried out by giving benzathine penicillin in 12 cases, oral doxycycline in 1 case and ceftriaxone in 2 cases. CONCLUSIONS: The prevalence of 28.3% of syphilis among newly diagnosed HIV cases indicates an emergency situation of this sexually transmitted infection. This requires a review of innovative public health strategies to control this re-emerging epidemic.